ENERAPAN PROGRAM TILAWAH, TAHFIDZ, MURAJA’AH (TTM) DALAM MENINGKATKAN HAFALAN AL-QUR’AN SISWA DI SEKOLAH MENENGAH PERTAMA AL QOLAM MUHAMMADIYAH GEMOLONG - Mey Nur Haliza; Nurul Latifatul Inayati; Saifudin Saifudin (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2021)
The implementation of the Recitation, Tahfidz, Muraja'ah (TTM) program occupies a position as a superior program implemented at Al Qolam Muhammadiyah Gemolong Middle School. The program is an attempt by the school to improve students' memorization of the Koran, so that at Al Qolam Muhammadiyah Gemolong Middle School it is mandatory for all students to take part in the program. The Recitation, Tahfidz, Muraja'ah (TTM) program at this school targets students to memorize 3 juz over a period of 3 years.This study aims to describe the implementation of the Recitation, Tahfidz, Muraja'ah (TTM) program and to identify the supporting and inhibiting factors for the implementation of Recitation, Tahfidz, Muraja'ah (TTM) in increasing students' memorization of the Koran at Al Qolam Muhammadiyah Gemolong Middle School in the academic year. 2021/2022. This research is classified as a type of qualitative field research (Field Research) with data collection methods through observation, interviews, and documentation. The validity of the data that researchers use is source triangulation. Data analysis was carried out using inductive analysis tools through the process of data reduction, data presentation, and drawing conclusions.The results of the study show that the implementation of the Recitation, Tahfidz, Muraja'ah (TTM) program at Al Qolam Muhammadiyah Gemolong Middle School has been going well, using the at-tartil method for recitations of the Qur'an, the talaqqi method for tahfidz Qur'an activities , and the takrir method for muraja'ah memorization of the Qur'an which is supported by facilities in the form of special time, a supportive school environment, and motivation from within the students and from the teacher. While the obstacles encountered were only a few such as students not being able to manage time properly, a little repetition of rote, and a feeling of laziness that sometimes approached.